TGM1/3-mediated transamidation of Exo70 promotes tumor metastasis upon LKB1 inactivation - Hou, Jihuan; Mei, Kunrong; Wang, Daxuan; Ke, Sunkui; Chen, Xiong; Shang, Jin; Li, Guixia; Gao, Yan; Xiong, Huifang; Zhang, Haoran; Chen, Lu; Zhang, Wenqing; et al. (Cell reports (Cambridge), 2024)
Exo70, a key exocyst complex component, is crucial for cell motility and extracellular matrix (ECM) remodeling in cancer metastasis. Despite its potential as a drug target, Exo70’s post-translational modifications (PTMs) are poorly characterized. Here, we report that Exo70 is transamidated on Gln5 with Lys56 of cystatin A by transglutaminases TGM1 and TGM3, promoting tumor metastasis. This modification enhances Exo70’s association with other exocyst subunits, essential for secreting matrix metalloproteinases, forming invadopodia, and delivering integrins to the leading edge. Tumor suppressor liver kinase B1 (LKB1), whose inactivation accelerates metastasis, phosphorylates TGM1 and TGM3 at Thr386 and Thr282, respectively, to inhibit their interaction with Exo70 and the following transamidation. Cantharidin, a US Food and Drug Administration (FDA)-approved drug, inhibits Exo70 transamidation to restrain tumor cell migration and invasion. Together, our findings highlight Exo70 transamidation as a key molecular mechanism and target and propose cantharidin as a therapeutic strategy with direct clinical translational value for metastatic cancers, especially those with LKB1 loss. [Display omitted] •TGM1 and TGM3 mediate transamidation of Exo70•Exo70 transamidation promotes cancer metastasis•LKB1 induces TGM1/3 phosphorylation to suppress Exo70 transamidation Hou et al. demonstrate that the transglutaminases TGM1 and TGM3 are responsible for the transamidation of the exocyst component Exo70, thereby regulating tumor cell invasion. Exo70 transamidation can be repressed by LKB1 phosphorylation of TGM1/3 or the application of cantharidin, an FDA-approved drug.